Antiarrhythmic drug responders among patients with recurrent atrial fibrillation after catheter ablation. (24th May 2021) - Park, Y; Yu, H; Kim, TH; Uhm, JS; Joung, B; Lee, MH; Pak, HN
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): The Ministry of Health and Welfare The National Research Foundation of Korea (NRF) Backgroud: Sinus rhythm (SR) can be maintained with antiarrhythmic drugs (AADs) in a considerable number of patients with recurrent atrial fibrillation (AF) after AF catheter ablation (AFCA). Purpose: We explored the characteristics and long-term outcomes of patients who maintained clinically acceptable rhythm control with AADs for 2 years. Methods: Among 2, 935 consecutive AAD-resistant patients who underwent a de novo AFCA, we included 512 recurrent patients (73.0% men, 59.2 ± 10.5 years old, 56.4% paroxysmal AF) who were followed up for over 2 years under AAD medications. Results: In total, 218 patients remained in SR (AAD-responders[2-yrs], 42.6%) and 294 had recurrent AF among whom, 162 underwent repeat procedures (redo-AFCA[AAD failure-2-yrs]). We also compared the AAD-responders[2-yrs] with 40 patients who underwent AFCA before AADs (redo-AFCA[Before AAD]). AAD-responders[2-yrs] were independently associated with an old age (odds ratio [OR] 1.02 [1.00-1.04] p = 0.037), paroxysmal AF (OR 1.51 [1.04-2.19] p = 0.003), and a delayed recurrence timing of > 18 months (OR 1.52 [1.04-2.22] p = 0.032). When comparing the AAD-responder[2-yrs] and redo-AFCA[AAD failure-2-yrs] groups, the recurrence pattern showed a convergence after 7 years. The overall rhythm outcome was better in the redo-AFCA[Before AAD] group than AAD group (log rank p = 0.013). Conclusion: Among the patients with recurrent AF after AFCA, over 40% remained in SR with AADs for 2 years, especially those who were old, those with a paroxysmal type, and those who had a delayed recurrence timing of >18 months after the de novo procedure.